Correlation between Tumor Necrosis Factor–Alfa and Anti-tyrosine Phosphatase with Obesity and Diabetes Type 2 - Ameen, Edrees Mohammad; Mohammed , Hassan Yaqoob (Iraqi Journal of Science, 2022)
This study was done to find a correlation between adipokines such as tumor necrosis- alpha (TNF-α)  and autoantigens such as anti-tyrosine phosphatase (IA2) with obesity and type 2 diabetes mellitus (T2DM). For this purpose, one hundred forty adult males were selected. 90 of them were diagnosed with type 2 diabetes and 50 healthy males). The subjects were divided into four groups. Group 1 had healthy controls with body mass index (BMI) between 18.5-25, group 2 had individuals who suffered from obesity only (BMI above 30), group 3 consisted of diabetes patients and group 4 had individuals who were diagnosed with both obesity and diabetes. The enzyme immunoassay was intended for quantification determination of TNF in serum. The results found a significantly (p≤0.001) higher  concentration of TNF-α  (21.01 ± 1.27 pg/ml) in patients suffering from both obesity and diabetes in comparison with the control (5.33 ± 0.67 pg/ml), obese patients (12.63 ± 1.35 pg/ml) and diabetes patients group (13.32 ± 0.83 pg/ml). Chi-square analysis found a significantly (p≤0.001) higher  prevalence of abnormal TNF-α in males suffering from both obesity and diabetes, 73.33% compared with diabetes non-obese males 31.1%. A  significant positive correlation (p≤0.01) was found between TNF-α with BMI (r= 0.65) and HbA1c (r= 0.57). No significant differences in IA2 concentration were observed between all groups.Also no significant correlation was observed between IA2 with BMI and HbA1c.